Corrosion protection of steel by volatile corrosion inhibitors: Vapor analysis by gas-diffusion microextraction and mass loss and electrochemical impedance in nacl deliquescence tests - Valente, Marco A.G. [UNESP]; Gonçalves, Luís M.; Filho, Juliano Passaretti [UNESP]; Cardoso, Arnaldo A. [UNESP]; Rodrigues, José A.; Fugivara, Cecilio S. [UNESP]; Benedetti, Assis V. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2020)
A new methodology using gas-diffusion microextraction (GDME) was developed for the analysis of volatile corrosion inhibitors (VCIs). The evaluation of the inhibition efficiency and corrosion rate (ν) was performed by NaCl deliquescence tests and correlated with measurements of polarization resistance (Rp) obtained from electrochemical impedance spectroscopy (EIS) analysis and with the pH resulting from the atmosphere of the inhibitor (pHGDME). The correlation obtained between ν and pHGDME indicates that the higher the value of pHGDME the lower the corrosion rate. The Raman spectra of steel was used to monitor in situ adsorption of VCI and the surface modifications caused by the inhibitors. The scanning electron microscopy (SEM) images corroborate the data of ν, both indicating that the cyclohexylamine vapor showed the best corrosion resistance performance.
Keywords: Corrosion; Derivatization; Steel; Vapor phase inhibitors; Volatile corrosion inhibitors